Ways to improve enterprise management - Malashenko, Natalia (My University, 2013)
Modern stage of economic development is characterized by deep changes in all spheres that affect enterprise management system.
Keywords: development; розвиток; развитие; enterprise; management; предприятие; управление; підприємство; управління